The application of the numerical wind wave model SWAN to a selected field case on the South African coast - Van der Westhuysen, A. J. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2002.